Financial security as a factor of military security - O. P. Getmanets; D. V. Korobtsova (Law and Safety)
Considering that ensuring the stability, reliability and efficiency of the financial system is a prerequisite for the country's defence capability, it has been noted that these positions are the basis for the interdependence of military and financial security. The essence, place and importance of financial security as a condition for ensuring military security have been investigated. The components of the military security system and the impact of the financial system on their functioning have been analysed. The author's own definition of the “financial security” concept and elements of the State’s financial security system have been proposed. The challenges and threats to the financial system of the State under martial law and the tasks of ensuring its stability, invincibility and effective functioning are considered. Based on the analysis of the Economic Security Strategy of Ukraine, it has been found that the state of the country’s financial security is assessed as unsatisfactory. It has been noted that the constant deficit of the state budget and the associated significant debt burden, insufficient development of long-term investment lending to the economy and the stock market, the growth of economic crime, and low financial culture in society are negative factors affecting the state of the financial system. It has been noted that different academic opinions on the constituent elements of financial security depend on the object of consideration. It has been noted that scientific analysis of financial security as a categorical institution has a significant impact not only on ensuring the country’s defence capability, but also on substantiating the current tasks of its organisational and legal support at the State level. General scientific theoretical methods have been used: system analysis aimed at identifying the object and subject of research, in particular, public finance; abstract and logical method – to provide scientifically sound generalisations and conclusions on the problems of legal regulation of financial security as a factor influencing military security and to define financial security measures as means of protecting the interests of a person and the State. The institutional, instrumental and functional components of financial security have been clarified. Attention has been drawn to the need to reform the system of state financial control bodies and improve the legal framework for monitoring public financial resources. It has been proved that there is a need for legislative regulation of relations on the circulation of public financial resources, and the directions of their orientation towards the actual tasks of ensuring military security have been substantiated.